Răspuns :
Răspuns:
[tex]\boldsymbol{ \red{ \big|2 - \sqrt{5} \big| = -(2 - \sqrt{5})}}[/tex]
Explicație pas cu pas:
Radical din 4 este 2: √4 = √2² = 2
Radical din 9 este 3: √9 = √3² = 3
Deoarece 4 < 5 < 9, atunci și √4 < √5 < √9, ceea ce înseamnă că
2 < √5 < 3, adică 2 - √5 < 0, de unde:
[tex]\big|2 - \sqrt{5} \big| = -(2 - \sqrt{5}) = -2+\sqrt{5} = \sqrt{5} - 2[/tex]
[tex]\it 4 < 5 \Rightarrow \sqrt4 < \sqrt5 \Rightarrow 2 < \sqrt5 \Rightarrow 2-\sqrt5 < 0 \Rightarrow |2-\sqrt5|=-2+\sqrt5[/tex]